Preparation process of moso bamboo charcoal ultra-high performance concrete

By pre-saturating the mosaic bamboo biochar and using specific mix ratios and curing processes in the concrete preparation process, the concrete and ease and strength problems caused by the strong water absorption of biochar are solved, and high compressive strength and resistance are achieved Ultra-high performance concrete with cracking performance.

CN119409460APending Publication Date: 2025-02-11ZHEJIANG UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411580230.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-11

Smart Images

  • Figure CN119409460A_ABST
    Figure CN119409460A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of moso bamboo charcoal ultra-high performance concrete, and relates to the technical field of ultra-high performance concrete. Soaking the moso bamboo charcoal in water, and draining water on the surface of the moso bamboo charcoal to obtain saturated surface-dried moso bamboo charcoal; 3 # quartz sand, 5 # quartz sand, quartz powder, cement, silica fume and saturated surface dry moso bamboo charcoal are sequentially added into a stirring pot, a water reducing agent is dissolved in water, the materials are added into the stirring pot in batches to be stirred, after the concrete has fluidity, mold filling and vibrating are conducted, indoor curing is conducted for 24 h, demolding and hot water curing are conducted for 7 days, and the moso bamboo charcoal ultra-high-performance concrete is prepared. Moso bamboo charcoal with saturated surface dry is utilized to bring water into the concrete, so that the risk of concrete cracking caused by non-uniform deformation due to self-shrinkage is reduced, and the effect of improving the compressive strength of the concrete is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ultra-high performance concrete, and in particular to a process for preparing ultra-high performance concrete made of bamboo biochar. Background Art

[0002] Ultra-high performance concrete is a new type of cement-based composite material with high strength, high durability and good toughness. Its ultra-high performance includes two aspects of "ultra-high" - ultra-high durability and ultra-high mechanical properties. Due to its good density, uniform material distribution, and significantly improved strength and durability compared to ordinary concrete, it is the most innovative cement-based engineering material in the past 30 years, achieving a major leap in the performance of engineering materials. It has broad application prospects.

[0003] Compared with traditional concrete, the strength of bamboo biochar ultra-high performance concrete is higher for the following reasons: 1. The moisture brought in by the saturated surface dry biochar provides internal self-curing and reduces shrinkage; 2. The moisture brought in by the saturated surface dry biochar promotes the full hydration of the cementitious material around the biochar particles to form a dense interface transition zone; 3. High-temperature water bath external curing promotes the secondary hydration of silica fume and improves the strength of concrete.

[0004] Ultra-high performance concrete adopts the principle of close packing for mix design. The aggregate is mainly fine quartz sand and the matrix is ​​highly dense. Such material properties give it excellent performance but also come with some disadvantages. For example, ultra-high performance concrete has poor volume stability due to its extremely low water-binder ratio. Similarly, compared with traditional concrete, bamboo biochar ultra-high performance concrete also has disadvantages: bamboo biochar has a large number of open pore structures inside, which makes it highly absorbent; if the moisture content of bamboo biochar is not well controlled, its high water absorption may further aggravate the shrinkage of concrete, resulting in more serious uneven deformation of concrete and cracking.

[0005] The volume stability problem mentioned above can be improved by adding pre-saturated bamboo biochar, which is a porous material with high water absorption. By replacing the fine aggregate with equal volume to introduce pre-saturated bamboo biochar particles, the water inside the biochar can enter the concrete during the later curing process, achieving the effect of internal curing, which has the potential to improve the volume stability problem of ultra-high performance concrete.

[0006] However, when porous materials are added to concrete for mixing, porous materials with a moisture content lower than the saturated surface dry state can easily absorb mixing water from the cement paste, thus affecting the effective water-binder ratio, making the workability of the concrete worse, and even causing the concrete to fail to be successfully mixed; porous materials with a moisture content higher than the saturated surface dry state will release excess water when mixing concrete, thereby changing the water-binder ratio of the concrete and reducing its strength. Therefore, it is necessary to pretreat the bamboo biochar so that it is just in the saturated surface dry state. However, how to make the bamboo biochar reach the saturated surface dry state is a difficult problem. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a bamboo biochar ultra-high performance concrete. The specially treated biochar can make the compressive strength of the ultra-high performance concrete reach more than 120MPa through internal curing, and can alleviate the self-shrinkage problem of concrete to a certain extent. It can be applied to buildings, bridges, tunnels, and even underground engineering and other fields.

[0008] To achieve the above object, the present invention provides the following technical solutions:

[0009] The bamboo biochar ultra-high performance concrete comprises the following raw materials in parts by weight:

[0010] Biochar 0-16.7 parts;

[0011] 916.5 parts of cement;

[0012] Silica fume 230.5 parts;

[0013] 3# quartz sand 1144.5 parts;

[0014] 5# quartz sand 115-127.6 parts;

[0015] 275 parts of quartz powder;

[0016] 8.33 parts of water reducing agent;

[0017] Water 183.52 parts;

[0018] The preparation process specifically comprises the following steps:

[0019] S1. Pre-saturate the biochar with water: weigh the biochar required for the experiment, soak it at 25°C for 24 hours, then take it out until the pre-saturated biochar stops dripping water, and calculate the water content of the pre-saturated biochar to obtain the saturated surface dry biochar;

[0020] S2. Add 3# quartz sand, 5# quartz sand and quartz powder to the mixer and stir for 3-5 minutes; add cement, silica fume and biochar to the mixing pot and stir for 3-5 minutes;

[0021] S3, dissolving the water reducer in water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 3-5 minutes, adding the remaining water reducer solution in batches until the slurry is completely fluidized in the mixer to obtain a bamboo biochar ultra-high performance concrete slurry;

[0022] S4. Conduct a mortar consistency test on the bamboo biochar ultra-high performance concrete slurry. Pour the concrete slurry into a 100mm×100mm×100mm cubic mold that has been pre-brushed with oil. Scrape off the excess concrete slurry that falls on the outside of the mold. Place the mold on a vibrator and add an appropriate amount of concrete slurry to the mold while vibrating until the concrete slurry in the mold no longer sinks during vibration. Use a scraper to smooth the concrete surface.

[0023] S5. Place the filled mold in the curing room for 24 hours, aim the air gun at the bottom slot of the mold and demould it;

[0024] S6. The demoulding crude concrete is placed in hot water for curing for 7 days to obtain the bamboo biochar ultra-high performance concrete.

[0025] Furthermore, the biochar is in a saturated surface dry state.

[0026] Furthermore, the cement is PO42.5 grade Portland cement.

[0027] Furthermore, the SiO2 content in the 3# quartz sand is greater than 99%, and its particle size is 2-4 mm.

[0028] Furthermore, the SiO2 content in the 5# quartz sand is greater than 99%, and its particle size is 20-40 meshes.

[0029] Furthermore, the SiO2 content in the quartz powder is greater than 99%, and the particle size is 200-300 meshes.

[0030] Furthermore, the water reducer is a polycarboxylic acid water reducer with a water content of less than 2.8% and a water reduction rate of more than 25%.

[0031] Furthermore, in step S3, the remaining water-reducing agent solution is added in batches, and the remaining water-reducing agent solution is added no less than 4 times to quickly wet the batch material and reduce dust.

[0032] Furthermore, in step S5, the temperature in the curing room is 25° C. and the air humidity is 95%.

[0033] Furthermore, in step S6, the temperature of the hot water is 90°C.

[0034] The present invention provides a pretreatment method for bamboo biochar, which can make the pre-saturated water-treated biochar reach a saturated surface dry state. The specific ideas are as follows:

[0035] Biochar, one of the ingredients required for the preparation of bamboo biochar ultra-high performance concrete, has strong water absorption. When mixing concrete, it easily absorbs mixing water from the mixture, thus affecting the workability of concrete and even causing the concrete to fail to mix successfully. Therefore, we quote the saturated surface dry state (there is no obvious water on the surface of biochar, but the internal pores are completely filled with water) to describe the general state of biochar. However, the saturated surface dry state is only an ideal state, and it is difficult to keep biochar in this state during the experiment.

[0036] Therefore, the difference between the water content of the biochar in the supersaturated state and the water content in the saturated surface dry state and the mixing water are considered as a whole. During the pretreatment of the biochar before the experiment, the biochar is placed in a supersaturated state, at which time its water content is greater than that in the saturated surface dry state. By calculating the difference between the water content in the supersaturated state and the saturated surface dry state, the actual amount of mixing water used in the concrete mixing process can be obtained.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] The present invention uses saturated surface-dry bamboo biochar to change the relative humidity and pore structure inside the concrete. The saturated surface-dry bamboo biochar brings moisture into the concrete, so that the concrete achieves the effect of internal curing, reduces the risk of cracking caused by uneven deformation due to shrinkage during the curing process, improves crack resistance, reduces the risk of self-shrinkage, and does not reduce the strength of the concrete. The ultra-high performance concrete with self-curing function obtained by the method provided by the present invention can be applied to reinforced concrete structural projects with limited curing conditions to a certain extent, such as buildings, bridges, tunnels and underground projects. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 , 2 This is a comparison diagram before and after the compression test of the bamboo biochar ultra-high performance concrete of the present invention.

[0040] Figure 3 A flow chart was prepared for the present invention. DETAILED DESCRIPTION

[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] In actual preparation, it is very difficult to achieve a saturated surface dry state, because the water on the surface of the carbon is constantly evaporating, and it is difficult to judge whether it is in a saturated surface dry state. After 24 hours of immersion, during the pre-saturation of biochar, there is a high probability that "the moisture content is higher than the saturated surface dry state" and "the moisture content is lower than the saturated surface dry state" will appear: "the moisture content is higher than the saturated surface dry state" will cause excess water to enter the concrete raw materials, increase its water-cement ratio, and reduce the 28-day strength; "the moisture content is lower than the saturated surface dry state" will cause the moisture carried inside the carbon to decrease, affecting the internal self-curing during the curing process.

[0043] Therefore, it is very important for the present invention to develop a complete set of "processes for making the pre-saturated water-treated biochar reach a saturated surface dry state". The following Table 1 is the operating idea of ​​the process:

[0044]

[0045] Table 1

[0046] Pre-saturate the biochar with water. Weigh the biochar required for the experiment and soak it at 25°C for 24 hours. After soaking, the pre-saturated biochar will not drip continuously. Take a small amount of wet charcoal and weigh it to record the mass m0. Put it in a mesh with a pore size of 0.15mm and put it in a drying oven preheated to 150°C until the weight no longer changes. Record the mass of the biochar after drying m1. The moisture content of the biochar after pre-saturation can be calculated by (m0-m1) / m1. After obtaining the moisture content of the charcoal and the required mass of dry charcoal, the mass of the wet charcoal that needs to be weighed can be calculated. On the other hand, because the weighed wet charcoal has more water than the saturated surface dry state biochar, the actual weighed mixing water = theoretical mixing water - theoretical dry carbon mass × (water content of biochar pre-saturated water - moisture content of biochar saturated surface dry state).

[0047] Determination of moisture content of "saturated surface dry biochar". Take 10 grams of dried charcoal, pour it into a volumetric flask and weigh m0, add water to the scale line and weigh the total weight m1 at T = 0h; after standing for 24h, add water to the scale line and finally weigh the total weight m2 at T = 24h.

[0048] Example 1

[0049] The bamboo biochar ultra-high performance concrete comprises the following raw materials in parts by weight:

[0050] 4.15 parts of saturated surface dry biochar;

[0051] 916.5 parts of cement;

[0052] Silica fume 230.5 parts;

[0053] 3# quartz sand 1144.5 parts;

[0054] 5# quartz sand 127.6 parts;

[0055] 275 parts of quartz powder;

[0056] 8.33 parts of water reducing agent;

[0057] Water 183.52 parts;

[0058] The preparation process specifically comprises the following steps:

[0059] S1. Pre-saturate the biochar with water: weigh the biochar required for the experiment, soak it at 25°C for 24 hours, then take it out until the pre-saturated biochar stops dripping water, and calculate the water content of the pre-saturated biochar to obtain the saturated surface dry biochar;

[0060] S2. Add 3# quartz sand, 5# quartz sand and quartz powder to the mixer and stir for 3 minutes; add cement, silica fume and biochar to the mixing pot and stir for 3 minutes;

[0061] S3, dissolving the water reducer in water and homogenizing to obtain a water reducer solution, pouring one-half of the water reducer solution into a mixer and stirring for 3 minutes, adding the remaining water reducer solution in batches until the slurry is completely fluidized in the mixer to obtain a bamboo biochar ultra-high performance concrete slurry;

[0062] S4. Conduct a mortar consistency test on the bamboo biochar ultra-high performance concrete slurry. Pour the concrete slurry into a 100mm×100mm×100mm cubic mold that has been pre-brushed with oil. Scrape off the excess concrete slurry that falls on the outside of the mold. Place the mold on a vibrator and add an appropriate amount of concrete slurry to the mold while vibrating until the concrete slurry in the mold no longer sinks during vibration. Use a scraper to smooth the concrete surface.

[0063] S5. Place the filled mold in a curing room at 25°C and 95% humidity for 24 hours, aim an air gun at the bottom slot of the mold to demould.

[0064] S6. The demoulding crude concrete is placed in 90° C. hot water for curing for 7 days to obtain the bamboo biochar ultra-high performance concrete.

[0065] Example 2

[0066] The bamboo biochar ultra-high performance concrete comprises the following raw materials in parts by weight:

[0067] 8.3 parts of saturated surface dry biochar;

[0068] 916.5 parts of cement;

[0069] Silica fume 230.5 parts;

[0070] 3# quartz sand 1144.5 parts;

[0071] 5# quartz sand 121.3 parts;

[0072] 275 parts of quartz powder;

[0073] 8.33 parts of water reducing agent;

[0074] Water 183.52 parts;

[0075] The preparation process specifically comprises the following steps:

[0076] S1. Pre-saturate the biochar with water: weigh the biochar required for the experiment, soak it at 25°C for 24 hours, then take it out until the pre-saturated biochar stops dripping water, and calculate the water content of the pre-saturated biochar to obtain the saturated surface dry biochar;

[0077] S2. Add 3# quartz sand, 5# quartz sand and quartz powder to the mixer and stir for 3 minutes; add cement, silica fume and biochar to the mixing pot and stir for 3 minutes;

[0078] S3, dissolving the water reducer in water and homogenizing to obtain a water reducer solution, pouring one-half of the water reducer solution into a mixer and stirring for 3 minutes, adding the remaining water reducer solution in batches until the slurry is completely fluidized in the mixer to obtain a bamboo biochar ultra-high performance concrete slurry;

[0079] S4. Conduct a mortar consistency test on the bamboo biochar ultra-high performance concrete slurry. Pour the concrete slurry into a 100mm×100mm×100mm cubic mold that has been pre-brushed with oil. Scrape off the excess concrete slurry that falls on the outside of the mold. Place the mold on a vibrator and add an appropriate amount of concrete slurry to the mold while vibrating until the concrete slurry in the mold no longer sinks during vibration. Use a scraper to smooth the concrete surface.

[0080] S5. Place the filled mold in a curing room at 25°C and 95% humidity for 24 hours, aim an air gun at the bottom slot of the mold to demould.

[0081] S6. The demoulding crude concrete is placed in 90° C. hot water for curing for 7 days to obtain the bamboo biochar ultra-high performance concrete.

[0082] Example 3

[0083] The bamboo biochar ultra-high performance concrete comprises the following raw materials in parts by weight:

[0084] saturated surface dry biochar 16.7 parts;

[0085] 916.5 parts of cement;

[0086] Silica fume 230.5 parts;

[0087] 3# quartz sand 1144.5 parts;

[0088] 5# quartz sand 115 parts;

[0089] 275 parts of quartz powder;

[0090] 8.33 parts of water reducing agent;

[0091] Water 183.52 parts;

[0092] The preparation process specifically comprises the following steps:

[0093] S1. Pre-saturate the biochar with water: weigh the biochar required for the experiment, soak it at 25°C for 24 hours, then take it out until the pre-saturated biochar stops dripping water, and calculate the water content of the pre-saturated biochar to obtain the saturated surface dry biochar;

[0094] S2. Add 3# quartz sand, 5# quartz sand and quartz powder to the mixer and stir for 3 minutes; add cement, silica fume and biochar to the mixing pot and stir for 3 minutes;

[0095] S3, dissolving the water reducer in water and homogenizing to obtain a water reducer solution, pouring one-half of the water reducer solution into a mixer and stirring for 3 minutes, adding the remaining water reducer solution in batches until the slurry is completely fluidized in the mixer to obtain a bamboo biochar ultra-high performance concrete slurry;

[0096] S4. Conduct a mortar consistency test on the bamboo biochar ultra-high performance concrete slurry. Pour the concrete slurry into a 100mm×100mm×100mm cubic mold that has been pre-brushed with oil. Scrape off the excess concrete slurry that falls on the outside of the mold. Place the mold on a vibrator and add an appropriate amount of concrete slurry to the mold while vibrating until the concrete slurry in the mold no longer sinks during vibration. Use a scraper to smooth the concrete surface.

[0097] S5. Place the filled mold in a curing room at 25°C and 95% humidity for 24 hours, aim an air gun at the bottom slot of the mold to demould.

[0098] S6. The demoulding crude concrete is placed in 90° C. hot water for curing for 7 days to obtain the bamboo biochar ultra-high performance concrete.

[0099] Comparative Example

[0100] Ultra-high performance concrete, comprising the following raw materials in parts by weight:

[0101] 916.5 parts of cement;

[0102] Silica fume 230.5 parts;

[0103] 3# quartz sand 1144.5 parts;

[0104] 5# quartz sand 127.6 parts;

[0105] 275 parts of quartz powder;

[0106] 8.33 parts of water reducing agent;

[0107] Water 183.52 parts;

[0108] The preparation process specifically comprises the following steps:

[0109] S1. Add 3# quartz sand, 5# quartz sand and quartz powder to the mixer and stir for 3 minutes; add cement, silica fume and biochar to the mixing pot and stir for 3 minutes;

[0110] S2, dissolving the water reducer in water and homogenizing to obtain a water reducer solution, pouring one-half of the water reducer solution into a mixer and stirring for 3 minutes, adding the remaining water reducer solution in batches until the slurry is completely fluidized in the mixer to obtain a bamboo biochar ultra-high performance concrete slurry;

[0111] S3. Conduct a mortar consistency test on the bamboo biochar ultra-high performance concrete slurry. Pour the concrete slurry into a 100mm×100mm×100mm cubic mold that has been pre-brushed with oil. Scrape off the excess concrete slurry that falls on the outside of the mold. Place the mold on a vibrator and add an appropriate amount of concrete slurry to the mold while vibrating until the concrete slurry in the mold no longer sinks during vibration. Use a scraper to smooth the concrete surface.

[0112] S4. Place the filled mold in a curing room at 25°C and 95% humidity for 24 hours, aim an air gun at the bottom slot of the mold to demould;

[0113] S5. The demoulding crude concrete is placed in 90° C. hot water for curing for 7 days to obtain the bamboo biochar ultra-high performance concrete.

[0114] The difference between this comparative example and Example 1 is that no saturated surface-dried biochar is added.

[0115] test:

[0116] 1. Determination of moisture content of biochar

[0117] The test results are shown in Table 2.

[0118] sample <![CDATA[m2(g)]]> <![CDATA[m1(g)]]> Moisture content (%) Example 1 623.9 610.1 138 Example 2 549.6 534.5 141 Example 3 588.0 573.9 141 Comparative Example 427.0 427.0 0

[0119] Table 2

[0120] 2. Autogenous Shrinkage

[0121] The test method refers to the following standards:

[0122] ASTM C1698-2009 Standard Test Method for Self-Stress of Cement Paste and Cement Mortar.

[0123] The test results are shown in Table 2.

[0124] 3. Compressive strength

[0125] After curing is completed, the concrete specimens are taken out of the hot water curing box.

[0126] Wipe off the surface moisture, check and measure the external dimensions and shape of the test piece, keep the two sides parallel, use the side faces during molding as the upper and lower pressure-bearing surfaces, and align the center of the test piece with the press geometry.

[0127] Start the press, apply the load, and control the loading speed at about 1KN / s. When the loading value drops from 1KN / s to a negative number (which means the specimen has been damaged), immediately close the oil supply valve and open the oil outlet valve. Record the data in time, and take the data at the peak value as the final compressive strength value.

[0128] Statistical data were collected, and the data measured on the three specimens were collated and the arithmetic mean was used as the compressive strength value of the specimens in this group.

[0129] The compressive strength test results of each group of specimens are shown in Table 3.

[0130] 4. Summary of results and conclusions

[0131]

[0132] Table 3

[0133] Autogenous shrinkage depends on the internal relative humidity and pore structure. The greater the internal relative humidity, the smaller the autogenous shrinkage. As shown in Table 3, the autogenous shrinkage of Examples 1-3 is significantly reduced compared to that of the comparative example, and the compressive strength of Examples 1-3 is significantly improved compared to the compressive strength of the comparative example, indicating that the saturated surface-dried bamboo biochar changes the relative humidity and pore structure inside the concrete, brings moisture into the concrete, reduces the autogenous shrinkage, and reduces the risk of cracking caused by uneven deformation of the concrete, thereby improving the compressive strength. The compressive strength of Examples 1 and 2 is significantly improved compared to Example 3, and the autogenous shrinkage of Example 2 is the smallest, indicating that the compressive performance of the concrete with the ratio of Example 2 is the most superior.

[0134] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0135] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A process for preparing ultra-high performance concrete using bamboo biochar, characterized in that: The composition comprises the following raw materials in parts by weight: Biochar 0-16.7 parts; 916.5 parts of cement; Silica fume 230.5 parts; 3# quartz sand 1144.5 parts; 5# quartz sand 115-127.6 parts; 275 parts of quartz powder; 8.33 parts of water reducing agent; Water 183.52 parts; The preparation process specifically comprises the following steps: S1. Pre-saturate the biochar with water: weigh the biochar required for the experiment, soak it at 25°C for 24 hours, then take it out until the pre-saturated biochar stops dripping water, and calculate the water content of the pre-saturated biochar to obtain the saturated surface dry biochar; S2. Add 3# quartz sand, 5# quartz sand and quartz powder to the mixer and stir for 3-5 minutes; add cement, silica fume and biochar to the mixing pot and stir for 3-5 minutes; S3, dissolving the water reducer in water and homogenizing to obtain a water reducer solution, pouring half of the water reducer solution into a mixer and stirring for 3-5 minutes, adding the remaining water reducer solution in batches until the slurry is completely fluidized in the mixer to obtain a bamboo biochar ultra-high performance concrete slurry; S4. Pour the bamboo biochar ultra-high performance concrete slurry into a 100mm×100mm×100mm cubic mold that has been pre-brushed with oil, scrape off the excess concrete slurry that falls on the outside of the mold, place it on a vibrator, and add an appropriate amount of concrete slurry to the mold while vibrating until the concrete slurry in the mold no longer sinks during vibration, and use a scraper to smooth the concrete surface; S5. Place the filled mold in the curing room for 24 hours, aim the air gun at the bottom slot of the mold and demould it; S6. The demoulding crude concrete is placed in hot water for curing for 7 days to obtain the bamboo biochar ultra-high performance concrete.

2. The process for preparing ultra-high performance concrete using bamboo biochar according to claim 1, characterized in that: The biochar is in a saturated surface dry state.

3. The process for preparing ultra-high performance concrete using bamboo biochar according to claim 1, characterized in that: The cement is PO42.5 grade silicate cement.

4. The process for preparing ultra-high performance concrete using bamboo biochar according to claim 1, characterized in that: The SiO2 content of the 3# quartz sand is greater than 99%, and its particle size is 2-4 mm.

5. The process for preparing ultra-high performance concrete using bamboo biochar according to claim 1, characterized in that: The SiO2 content of the 5# quartz sand is greater than 99%, and its particle size is 20-40 meshes.

6. The process for preparing ultra-high performance concrete using bamboo biochar according to claim 1, characterized in that: The SiO2 content in the quartz powder is greater than 99%, and the particle size is 200-300 meshes.

7. The process for preparing ultra-high performance concrete from bamboo biochar according to claim 1, characterized in that: The water reducer is a polycarboxylic acid water reducer with a water content of less than 2.8% and a water reduction rate of more than 25%.

8. The process for preparing ultra-high performance concrete using bamboo biochar according to claim 1, characterized in that: In step S3, the remaining water-reducing agent solution is added in batches. In order to quickly wet the batch material and reduce dust, the remaining water-reducing agent solution is added in no less than 4 times.

9. The process for preparing ultra-high performance concrete from bamboo biochar according to claim 1, characterized in that: In step S5, the temperature in the curing room is 25° C. and the air humidity is 95%.

10. The process for preparing ultra-high performance concrete from bamboo biochar according to claim 1, characterized in that: In step S6, the hot water temperature is 90°C.